Synthesis of reactive DOPO-based flame retardant and its application in rigid polyisocyanurate-polyurethane foam - Qian, Xue; Liu, Qiang; Zhang, Laibao; Li, Hui; Liu, Jiwen; Yan, Shouke (Polymer degradation and stability, 2022)
•A reactive low-molecular flame-retardant polyester diol based on DDP was synthetized.•The flame-retardant RPUF-PIR reached a high LOI value of 28.0 vol% with a 3.5 wt% phosphorus content and the NCO/OH ratio of 3.5.•The density and compressive strength of PIRs were improved with the content of phosphorus increased from 0 to 3.75 wt% (NCO/OH = 2.5). In this study, a reactive flame-retardant diol (BEOPMS) was synthesized by the esterification reaction of 9,10-dihydro-10-[2,3-di(hydroxycarbonyl)propyl]-10- phospha-phenanthrene-10-oxide with diethylene glycol. The flame-retardant effect of it combined with polyaryl polymethylene isocyanate (PMDI) were tested for rigid polyisocyanurate-polyurethane foams (PIRs) fabricated via a one-step process. The higher limiting oxygen index (LOI) and char residue yield value of flame-retardant rigid polyurethane foam (FRPUF) (21.0 vol% and 21.9 wt%, respectively) at 3.5 wt% phosphorus content compared to those of the pure rigid polyurethane foam (RPUF) (17.0 vol% and 16.3 wt%, respectively), illustrating the great effect of BEOPMS on improving the flame retardancy of the foams. At a 3.5 molar ratio of NCO/OH and 3.5 wt% content of phosphorus, an even higher LOI value of PIR (28.0 vol%) with a highest char residue yield (44.7 wt%) was obtained. The flame-retardant mechanism was discussed according to the scanning electron microscope (SEM), energy dispersive spectrometer (EDS), cone calorimeter (CC) and thermal gravimetric analysis-Fourier-transform infrared analyses (TG-IR). It is recognized that the isocyanurate ring groups can improve the thermostability of resultant PIRs, and increase the char residue yield in combination with the higher content of PMDI. Meanwhile, the thermal degradation of BEOPMS produces phosphate in condensed phase and released PO and PO₂ free radicals, which inhibits the free radical chain reactions in the gas phase and thus enables a superior flame retardancy effect for polyurethane foams. [Display omitted]